2017
DOI: 10.1128/aac.01293-16
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Probiotic Strain ED1a in Pigs Has a Limited Impact on the Gut Carriage of Extended-Spectrum-β-Lactamase-Producing E. coli

Abstract: Four trials were conducted to evaluate the impact of Escherichia coli probiotic strain ED1a administration to pigs on the gut carriage or survival in manure of extended-spectrum-␤-lactamase-producing E. coli. Groups of pigs were orally inoculated with strain E. coli M63 carrying the bla CTX-M-1 gene (n ϭ 84) or used as a control (n ϭ 26). In the first two trials, 24 of 40 E. coli M63-inoculated pigs were given E. coli ED1a orally for 6 days starting 8 days after oral inoculation. In the third trial, 10 E. coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 35 publications
0
23
1
Order By: Relevance
“…5). Spread of bla CTX-M -carrying plasmid among commensal E. coli populations had already been observed in orally inoculated piglets with an E. coli strain carrying bla CTX-M-1 gene (61). It has been shown both in vitro and in vivo in mice that conjugation frequencies vary across plasmid, donor, and recipient combinations (85).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). Spread of bla CTX-M -carrying plasmid among commensal E. coli populations had already been observed in orally inoculated piglets with an E. coli strain carrying bla CTX-M-1 gene (61). It has been shown both in vitro and in vivo in mice that conjugation frequencies vary across plasmid, donor, and recipient combinations (85).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of bla CTX-M carrying plasmid may have happened during our study, but as we focused only on E. coli clones displaying a phenotype of ESBL production, we cannot estimate the magnitude of such loss rate. Studies showed that spontaneous loss happens rarely in vivo, even when ESBL-producing strains compete with plasmid-free strains, as shown in pigs, rabbits and lambs (60)(61)(62)(63). A modulation of the cost by a selective switch off of horizontally acquired gene expression (64,65) could also explain why no association was found between genes and the ability for a clone to colonize many calves nor to persist in farms.…”
Section: Dynamics Of Esbl Prevalence In Calvesmentioning
confidence: 99%
“…They were identified with an E. coli -specific PCR ( Furet et al., 2009 ); the presence of the bla CTX − M-1 gene was screened for using PCR ( Woodford, Fagan & Ellington, 2006 ). Moreover, the isolates obtained from pigs were also tested by PCRs specific to the E. coli ED1a or EcN strains ( Mourand et al., 2017 ). Finally, for all faecal samples collected on day 49 and rectum samples on day 58, a cell lysate was prepared from all the pooled colonies obtained on non-supplemented MC plates, and for manure samples, a suspension was prepared from all the pooled colonies of the MC—CTX plates for PCR analysis, as described below.…”
Section: Methodsmentioning
confidence: 99%
“…Each DNA extract was quantified using the NanoDrop 2000 spectrophotometer (Thermo Scientific) then adjusted to a concentration of 10 ng/µL, before storage at −20 °C. E. coli, E. coli ED1a and E. coli EcN were quantified in faeces, PM and manure samples from piglets according to Mourand et al. (2017) .…”
Section: Molecular Analysismentioning
confidence: 99%
See 1 more Smart Citation